1996
DOI: 10.1246/cl.1996.139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3-Diarylquinone by Palladium Catalyzed Cross-Coupling of Dibromoquinones with Heteroarylstannanes

Abstract: The synthesis of various kinds of both symmetrical and asymmetrical diarylquinones has been realized by the palladium catalyzed cross-coupling of 2,3-dibromoquinones with tributylstannylheteroaromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Single and double coupling reactions involving stannylthiophenes (and -pyrroles) with dibromoquinones have been reported [88]; another less conventional substrate used was a 2,6-dibromophosphosphabenzene (Scheme 4-30; here also single and double couplings were reported, as was the coupling of a 2-stannyl-pyridine) [89].…”
Section: Scheme 4-29mentioning
confidence: 97%
“…Single and double coupling reactions involving stannylthiophenes (and -pyrroles) with dibromoquinones have been reported [88]; another less conventional substrate used was a 2,6-dibromophosphosphabenzene (Scheme 4-30; here also single and double couplings were reported, as was the coupling of a 2-stannyl-pyridine) [89].…”
Section: Scheme 4-29mentioning
confidence: 97%
“…The reaction between organotin compounds and various electrophiles takes place under neutral conditions in the presence of catalytic amounts of palladium [24] and has a high degree of selectivity. Both symmetricaly [25,26] and unsymmetrically substituted quinones [26] can be obtained by this method. The usual catalyst is Pd(PPh 3 ) 4 .…”
Section: Reactions Of Haloquinones With Heteroarylstannanes Catalymentioning
confidence: 99%
“…of tributylstannylheteroarene with yields of ~70%. Diheteroarylbenzoquinones 3 with various substituents at positions 2 and 3 are produced according to the following scheme [25,26]: In the reaction of 2,5-dibromobenzoquinone with an excess of 3-indolylstannane under the standard conditions for the Stille reaction the monosubstituted product is formed initially, and the 2,5-disubstituted benzoquinone 4 is then formed more slowly [27]. By this two-stage method it is possible to obtain 2,5-bisindolylquinones with various alkyl substituents at the nitrogen atom.…”
Section: Reactions Of Haloquinones With Heteroarylstannanes Catalymentioning
confidence: 99%
“…More recently, Yoshida et al have published the palladium-catalysed cross couplings of aryl and heteroarylstannanes with 2,3-dibromo-1,4-quinones to give a number of 2,3-bisaryl-1,4-naphthoquinones. [3,4] Similarly, Stagliano et al have reported a three-step procedure for the preparation of 2,3-bisaryl-1,4-quinones involving palladium-catalysed cross couplings of arylstannanes with activated 1,4-naphthoquinones, [5] and they have recently exploited this methodology in the synthesis of conocurvone analogues. [6] We sought a simple one-step procedure to 2,3-bisaryl-1,4naphthoquinones from readily available starting materials, that would also be amenable to a wide range of functional groups, and would avoid the use of tin.…”
Section: Introductionmentioning
confidence: 99%